Halal Product Guarantee to the Development of Small and Medium Enterprises Business in Indonesia - Ridwan Arifin; Waspiah; Salsabila Fakhriyyah Ar-raidah; Vania Shafira Yuniar (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This study to analyze the guarantee of halal products for SMEs development in Indonesia. This normative juridical research uses legislation and conceptual approach. Sources of data are obtained from primary and secondary legal materials. The research results showed halal product guarantee for SMEs is very important because with halal certification, then a product has have gained legality and legal protection. The importance of halal product guarantees for SMEs in Indonesia, i.e.: Indonesian population is dominated by Muslims; the awareness of the Indonesian Muslim in consuming halal products; Indonesia has many SMEs; non-Muslim consumers consider that every halal product is of high quality, safe and hygienic; and the role of religious norms in the implementation of halal product guarantees. Law Number 33 of 2014 concerning Guarantee of Halal Products, requires SMEs to have halal certification so that BPJPH gave the authority to do socialization and assistance of halal certification. However, it’s experiencing problems, i.e.: complicated requirements, limited facilities, the lack of information about the procedures for filing the halal label and high costs for the halal certification process. Therefore, the government must assist and facilitate SMEs to obtain the halal certificate, so there is legal certainty in developing their business.